TRAINING OF QUALIFIED SPECIALISTS AT ORENBURG STATE UNIVERSITY - Editorial Article (Высшее образование в России)
The rector of Orenburg State University has granted an interview to the journal. The main themes covered the issues concerning the role of the university in the regional development, university’s responsiveness to the interests and requirements of the main stakeholders in vocational education. The university became the winner of the competition “Cadres for regions” conducted by the Ministry of education and science of Russian Federation.